Traditional Chinese medicine method of tonifying kidney for hypertension: Clinical evidence and molecular mechanisms - Wang, Qingqing; Lin, Jianguo; Li, Cheng; Lin, Mingshan; Zhang, Qing; Zhang, Xiaoxiao; Yao, Kuiwu (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is the most common chronic disease. A large amount of evidence showed that traditional Chinese medicine (TCM) method of tonifying kidney (TK) combined with routine treatment is more effective and safer in the treatment of hypertension. This study integrated meta-analysis, data mining, and network pharmacology to explore the efficacy and potential mechanisms of TK in the treatment of hypertension. Meta-analysis was performed to explore the efficacy and safety of TK combined with routine treatment in the treatment of hypertension. Data mining was used to screen the core herbs of the TK. Network pharmacology was used to predict the antihypertensive mechanism of TK core herbs. A total of 18 studies with 2,024 patients were included in this study. Meta-analysis showed that TK combined with routine treatment was superior to routine treatment alone in lowering blood pressure (systolic and diastolic blood pressures), lowering blood lipids (total cholesterol, triglyceride, low-density lipoprotein cholesterol), improving vascular endothelial functions (nitric oxide, endothelin) and TCM symptoms (headache dizziness, soreness, and weakness of waist and knees). In addition, TK was safe and has no obvious adverse reactions. Data mining showed that the core herbs of TK were Eucommia ulmoides Oliv. (Duzhong), Vitex negundo L. (Huangjing), Taxillus chinensis (DC.) Danser (Sangjisheng), Ligustrum lucidum W.T.Aiton (Nuzhenzi), Astragalus mongholicus Bunge (Huangqi), Rehmannia glutinosa (Gaertn.) DC. (Shudihuang). Network pharmacology predicted that core herbs antihypertensive components were oleanolic acid, ursolic acid, and civetone, and the antihypertensive targets were NOS3, NOS2, MMP9, TNF, PTGS2, HMOX1. In addition, the antihypertensive targets were enriched in cGMP-PKG signaling pathway, calcium signaling pathway, aldosterone-regulated sodium reabsorption, HIF-1 signaling pathway. In conclusion, TK combined with routine treatment for hypertension is effective and safe. The mechanism of TK may be related to GMP-PKG signaling pathway, calcium signaling pathway, aldosterone-regulated sodium reabsorption. On the premise of syndrome differentiation and treatment, it is promising to treat hypertension with TK. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022358276].